Chiral gold nanoparticles for alkaline electrolysis water oxygen evolution reaction catalyst and synthesis method and application thereof
By combining structural design and chiral characteristics in nanomaterials, the chiral gold nanobranch-type triangle plates are solved, and the complex and unstable synthesis of gold nanotriangle plates in the prior art is achieved, and high-efficiency catalytic oxygen evolution reaction and good stability.
Patent Information
- Application Number
- CN202411519283.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The method of synthesizing gold nanotriangle plates in the prior art is complicated and difficult to control conditions, resulting in unstable catalysts and difficult to store for a long time.
By combining the structural design and chiral characteristics of nanomaterials, using cysteine as an inducer, chiral gold nanobranch-type triangle plates were synthesized through a seed-mediated site-selective chiral growth system.
A highly efficient catalytic oxygen evolution reaction was achieved, which significantly improved the catalytic performance, and the overpotential and taffel slope were better than the commercial catalyst ruthenium dioxide, and had good stability.
Smart Images

Figure CN119387603A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano material preparation, and in particular to chiral gold nanoparticles used as catalysts for oxygen evolution reaction in alkaline water electrolysis, and a synthesis method and application thereof. Background Art
[0002] Electrochemical catalytic water splitting is currently a highly researched field due to the great potential of hydrogen as an ideal zero-carbon fuel. The rate-determining step of water splitting is the oxygen evolution reaction (OER), which involves the transfer of four electrons and the formation of complex intermediates (including peroxides and superoxides) throughout the process, rather than the two-electron transfer process of the hydrogen evolution reaction. Therefore, the synthesis of efficient OER catalysts is of great significance to improve the selectivity, suppress the formation of by-products, and simultaneously reduce the overpotential energy loss during the electrochemical reaction.
[0003] The importance of hydrogen energy lies in its potential as a clean and sustainable fuel source, providing a pathway to mitigate climate change and reduce dependence on fossil fuels. Electrochemical catalytic water splitting is a key process for hydrogen production and holds great promise in this regard. Specifically, the rate-determining step of water splitting, the oxygen evolution reaction (OER), involves four electron transfers and the formation of complex intermediates, such as peroxides and superoxides. Therefore, the synthesis of efficient OER catalysts is of great significance to improve selectivity, suppress by-product formation, and simultaneously reduce overpotential energy losses during the electrochemical reaction.
[0004] CN104625086A discloses a method for preparing a gold nano triangular sheet, a gold nano disc and a gold nano hexagonal sheet. The method for preparing the gold nano triangular sheet comprises: first preparing a nano gold seed solution with a sodium citrate aqueous solution, a tetrachloroauric acid aqueous solution and a sodium borohydride aqueous solution; then preparing a gold nano triangular sheet solution with the prepared seed solution and a hexadecyltrimethylammonium bromide aqueous solution, a tetrachloroauric acid aqueous solution, a potassium iodide or sodium iodide aqueous solution, a sodium hydroxide aqueous solution and an ascorbic acid aqueous solution; and discarding the supernatant to obtain a gold nano triangular sheet. However, this method is difficult to synthesize, has many synthesis steps, and requires very precise control of the details of the conditions. In addition, the synthesized gold nano triangular sheet is difficult to completely separate from the reactants, so the gold nano triangular sheet is not convenient for long-term storage (more than three months), otherwise it may deteriorate.
[0005] Therefore, there is an urgent need for a method for preparing chiral gold nanoparticles with a simple synthesis method in order to prepare chiral gold nanoparticles with excellent catalytic properties that can be used for oxygen evolution reaction. Summary of the invention
[0006] In view of the differences existing in the prior art, the purpose of the present invention is to provide a chiral gold nanoparticle used as a catalyst for oxygen evolution reaction in alkaline water electrolysis, and a synthesis method and application thereof. The present invention combines the structural design of nanomaterials with chiral characteristics, and proposes a novel catalytic strategy for oxygen evolution reaction. By enhancing electron transport and spin selectivity, efficient catalysis of oxygen evolution reaction is achieved, providing a new idea for the design of nanocatalysts. The present invention is an elemental noble metal chiral catalyst for oxygen evolution reaction, namely, a chiral gold dendritic triangular nanoplate. The catalyst shows an extremely high chiral optical signal (100-150mdeg) in circular dichroism spectrum (circular dichroism spectrum) measurement. L-type and D-type chiral gold nano-branched triangle plates show obvious performance differences in oxygen evolution reaction catalysis, and the performance of L-type gold nano-branched triangle plates is even comparable to that of commercial catalysts.
[0007] The present invention is achieved through the following technical solutions:
[0008] The first object of the present invention is to provide a method for synthesizing chiral gold nanoparticles for use as catalysts for oxygen evolution reaction in alkaline water electrolysis, the method comprising the following steps:
[0009] (1) adding tetrachloroauric acid trihydrate and trisodium citrate hydrate to water, mixing the mixture, adding the mixture to water, then adding ice-cold sodium borohydride solution under stirring, heating the solution in a water bath after stirring, and then storing the gold seed solution at low temperature;
[0010] (2) adding the gold seed solution obtained in step (1) to a mixed solution A containing cetyltrimethylammonium bromide, tetrachloroauric acid, sodium hydroxide, potassium iodide and ascorbic acid, stirring and mixing them uniformly, taking the mixed solution, adding it to a mixed solution B containing cetyltrimethylammonium bromide, tetrachloroauric acid, sodium hydroxide, potassium iodide and ascorbic acid, stirring and mixing them uniformly, and then introducing the entire solution into a mixed solution C composed of cetyltrimethylammonium bromide, tetrachloroauric acid, sodium hydroxide, potassium iodide and ascorbic acid, stirring the solution, then heating it in a water bath, centrifuging the product, removing the supernatant, and storing the substrate in the cetyltrimethylammonium bromide solution to obtain a solution D;
[0011] (3) Take water, add hexadecyltrimethylammonium bromide, tetrachloroauric acid and ascorbic acid in sequence, then stir, inject the cysteine solution into the solution to form a gold nanotriangle, stir for 1 to 2 minutes, then take the solution D obtained in step (2) and add it to the mixed solution, stir, and then stand in a water bath to obtain a chiral gold nanoparticle dispersion, centrifuge the obtained chiral gold nanoparticle dispersion to remove unreacted reagents, remove the supernatant, and redisperse in the hexadecyltrimethylammonium bromide solution to obtain chiral gold nanoparticles.
[0012] Furthermore, the gold seed solution obtained in step (1) is a solution containing gold seeds, and the average particle size of the gold seeds in the gold seed solution is 30 nanometers to 60 nanometers.
[0013] Furthermore, the nanoparticles in the solution D obtained in step (2) are mostly triangular, with a small portion being pentagonal or hexagonal, and the average particle size of the nanoparticles in the solution D is 60 nanometers to 120 nanometers.
[0014] Furthermore, in step (3), when the cysteine in the cysteine solution is L-cysteine, the chiral gold nanoparticles formed are L-type gold nanobranch particles, and the L-type gold nanobranch triangle is snowflake-shaped, with the branches twisted in a clockwise direction and an average particle size of 400 to 600 nanometers.
[0015] Furthermore, in step (3), when the cysteine in the cysteine solution is D-cysteine, the chiral gold nanoparticles formed are D-type gold nanobranch particles, and the D-type gold nanobranch triangle is snowflake-shaped, with the branches twisted in the counterclockwise direction and an average particle size of 400 to 600 nanometers.
[0016] Furthermore, the chiral gold nanoparticles obtained in step (3) are chiral gold nanoparticles capable of detecting chiral optical signals, and when the absorption is around 0.5 to 1.5, the circular dichroism signal is between 100 and 150 mdeg.
[0017] Furthermore, the chiral gold nanoparticles obtained in step (3) have a main crystal face exposed in X-ray diffraction characterization as a gold (1 1 1) crystal face. Furthermore, the synthesis method specifically comprises the following steps:
[0018] (1) 0.032 g of tetrachloroauric acid trihydrate and 0.0294 g of trisodium citrate hydrate were added to 20 mL of water, and after mixing, 2 mL of the solution was added to water (36.0 mL), and then an ice-cold sodium borohydride solution (0.1 M, 1.0 mL) was added under magnetic stirring, wherein the temperature of the sodium borohydride solution was 0.5° C. After stirring for 2 minutes, the solution was placed in a water bath at 30° C. for 4 hours, and then placed in a refrigerator at 0 to 2° C. to store the gold seed solution;
[0019] (2) 0.5 mL to 2 mL of the gold seed solution was added to a mixed solution A containing hexadecyltrimethylammonium bromide (0.05 to 1 M, 9 mL), tetrachloroauric acid (0.01 M, 0.25 mL), sodium hydroxide (0.1 M, 0.05 mL), potassium iodide (0.01 M, 0.05 mL) and ascorbic acid (0.1 to 0.2 M, 0.05 mL). After mixing evenly with magnetic stirring, 1 mL of the solution was taken and added to a mixed solution A containing hexadecyltrimethylammonium bromide (0.05 to 1 M, 9 mL), tetrachloroauric acid (0.01 M, 0.25 mL), sodium hydroxide (0.1 M, 0.05mL), potassium iodide (0.01M, 0.05mL) and ascorbic acid (0.1-0.2M, 0.05mL) in a mixed solution B, after magnetic stirring and mixing, the whole solution is introduced into a mixed solution C composed of hexadecyltrimethylammonium bromide (0.05-1M, 90mL), tetrachloroauric acid (0.01M, 2.5mL), sodium hydroxide (0.1M, 0.5mL), potassium iodide (0.01M, 0.5mL) and ascorbic acid (0.1-0.2M, 0.5mL), the solution is magnetically stirred for 5 minutes, and then water bathed at 30°C for 24 hours. After 24 hours, the product is separated by centrifugation at a speed of 4000-5000rpm for 5 minutes, the supernatant is removed, and the substrate is stored in 1mM 100mL hexadecyltrimethylammonium bromide solution to obtain solution D;
[0020] (3) Take 34.77 mL of deionized water, add hexadecyltrimethylammonium bromide (8 mL, 10 mmol), tetrachloroauric acid (2 mL, 10 mM) and ascorbic acid (5 mL, 40 mM) in sequence, then stir at a speed of 50-100 rpm for 1-2 minutes, inject 3 μL of 0.5-1 mM cysteine (L-cysteine or D-cysteine) solution into the solution to form a gold nanobranch-shaped triangle, stir at a speed of 50-100 rpm for 1-2 minutes, then take 300-600 μL of solution D obtained in step (2) and add it to the mixed solution, and stir for 30 seconds, then stand in a water bath at 30°C for 1 hour, centrifuge the obtained chiral gold nanoparticle dispersion at 2500 rpm for 5 minutes to remove unreacted reagents, remove the supernatant, and redisperse it in 1 mM 10 mL hexadecyltrimethylammonium bromide solution to obtain chiral gold nanoparticles, which are stored at room temperature.
[0021] Furthermore, in step (3), 3 μL of 0.5-1 mM cysteine (L-cysteine or D-cysteine) solution is injected into the solution to form an L-type gold nanobranched triangle (L-type chiral gold nanoparticles are subsequently obtained, and the L-type chiral gold nanoparticles are L-type gold nanobranched particles) or a D-type gold nanobranched triangle (D-type chiral gold nanoparticles are subsequently obtained, and the D-type chiral gold nanoparticles are D-type gold nanobranched particles), and stirred at a rotation speed of 50-100 rpm for 1-2 minutes (for achiral gold nanoconcave triangles, cysteine is not added in this step, and achiral gold nanoparticles are subsequently obtained, and the achiral gold nanoparticles are achiral gold nanoconcave particles).
[0022] Furthermore, the L-type gold nanoparticles and D-type gold nanoparticles obtained in step (3) are snowflake-shaped, with the branches twisted clockwise and counterclockwise, respectively, and the average particle size is 400 to 600 nanometers. The achiral gold nanoparticles are polygonal flat, with no fixed twisting direction, and the average particle size is 300 to 500 nanometers.
[0023] Furthermore, the L-type gold nanobranched triangle plate and the D-type gold nanobranched triangle plate obtained in step (3) can detect chiral optical signals, and when the absorption is about 0.5 to 1.5, the circular dichroism spectrum signal is 100 to 150 mdeg. However, the non-chiral gold nanoconcave triangle plate nanoparticles have no obvious chiral optical signal, and when the absorption is about 0.5 to 1.5, the circular dichroism spectrum is 0 to 20 mdeg.
[0024] Furthermore, the three chiral and achiral nanoparticles obtained in step (3): L-type gold nanobranched particles, D-type gold nanobranched particles, and achiral gold nanoconcave particles have a main crystal plane exposed in X-ray diffraction characterization as the gold (1 11) crystal plane.
[0025] Furthermore, the chiral gold nanoparticles obtained showed good catalytic performance in oxygen evolution reaction. 7 to 8 mg of the three chiral gold nanoparticles or achiral gold nanoparticles obtained were loaded onto nickel foam 1×1 cm 2 On a square area of , perfluorosulfonic acid-polytetrafluoroethylene copolymer was used as a binder, and electrochemical measurements were performed at room temperature in a 1M potassium hydroxide (pH = 14) solution. Scanning was performed at a scan rate of 5 mV / s, and when the current density was 10 mA per square centimeter, the overpotential of the L-type chiral gold nanoparticles was 355.7 mV, even lower than the control group (387.7 mV) in which the same amount of commercial catalyst ruthenium dioxide was drop-cast, as well as the D-type chiral gold nanoparticles (449.1 mV) and the achiral gold nanoparticles (455.3 mV).
[0026] Furthermore, the obtained chiral gold nanoparticles exhibited good catalytic performance in oxygen evolution reaction. The Tafel slope of L-type chiral gold nanoparticles at 10 mA per square centimeter was 61.72 mV per decade, which was significantly lower than the 136.76 mV per decade of the control group in which an equal amount of commercial catalyst ruthenium dioxide was drop-cast. The Tafel slopes of D-type chiral gold nanoparticles and achiral gold nanoparticles were 149.4 mV per decade and 228.0 mV per decade, respectively, and the Tafel slope of D-type chiral gold nanoparticles was not significantly different from that of ruthenium dioxide. The Tafel slope is the rate of change of overpotential with the logarithm of current density, which reveals the exchange current density and reaction kinetics of the electrochemical reaction of a specific catalyst.
[0027] The second object of the present invention is to provide a chiral gold nanoparticle, which is prepared by a chiral gold nanoparticle synthesis method for a catalyst for oxygen evolution reaction in alkaline water electrolysis.
[0028] The third object of the present invention is to provide an application of chiral gold nanoparticles for alkaline water electrolysis oxygen evolution reaction catalyst, the chiral gold nanoparticles are prepared by a chiral gold nanoparticle synthesis method for alkaline water electrolysis oxygen evolution reaction catalyst, and the chiral gold nanoparticles are used as oxygen evolution reaction catalyst in an alkaline electrolyte.
[0029] Furthermore, at a current density of 10 mA per square centimeter, the overpotential of the chiral gold nanoparticles is 355.7 mV to 449.1 mV.
[0030] Furthermore, the Tafel slope of the chiral gold nanoparticles at 10 milliamperes per square centimeter is 61.72 millivolts per decade to 149.4 millivolts per decade.
[0031] The technical concept of the present invention is as follows:
[0032] Among chiral nanomaterials, gold nanoparticles have received the most attention. Recently, chiral gold nanoparticles with strong optical activity and high circular dichroism values have been widely studied. However, they are rarely used as chiral catalysts in the field of oxygen evolution reaction, which makes them of high research value. Gold itself is a noble metal with good oxygen evolution reaction performance, suitable adsorption and desorption energies (favorable for the smooth progress of oxygen evolution reaction catalysis), and high stability. The strong chirality of gold makes it possible to have high spin polarization. Therefore, we speculate that gold nanostructures can be used as ideal chiral catalysts for electrocatalytic water splitting reactions. The good lattice structure and excellent conductivity make them promising candidates. The surface properties of gold catalysts can be easily manipulated by changing the morphology, size, crystal structure and surface modification, thereby effectively adjusting and optimizing the catalytic performance. In addition, when subjected to an electric field to cause the electron cloud density to be distorted, they are less subject to irregular lattice structures caused by heterojunctions, doping or vacancies, which helps to better transmit spin properties. In addition, noble metal catalysts usually show high selectivity due to their empty d orbitals, which facilitate bond formation with other radicals, as the reactivity of the catalyst is highly correlated with the proportion of d electrons participating in coordination. Noble metals have 5d or 7d orbitals, which have larger radii than the 3d orbitals of transition catalysts, allowing the noble metals to have a higher proportion of d orbital electrons in coordination. In addition, the stability of gold allows its repeated use, making it a practical and sustainable choice for electrochemical water splitting applications.
[0033] Therefore, the present invention provides a chiral gold nanoparticle and a preparation method and application thereof.
[0034] The present invention uses cysteine as an inducer and synthesizes a chiral gold nano-branched triangle plate through a seed-mediated site-selective chiral growth system. First, in the presence of potassium iodide, a gold triangular nanoplate (gold nano-triangle plate) is synthesized by gold seed crystals. The prepared gold nano-triangle plate has a uniform triangular plate structure with exposed {111} plane facets and an average side length of 172±24nm. The gold nano-triangle plate is introduced into a growth solution of tetrachloroauric acid, ascorbic acid, hexadecyltrimethylammonium bromide and chiral molecules to start the growth of the chiral gold nano-triangle plate. L / D-cysteine is used as a chiral inducer to interact with the gold surface enantioselectively and drive the formation of a propeller structure with highly twisted chiral characteristics. Growing branches or twigs along a specific direction on the gold nanotriangle plate leads to the formation of anisotropic chiral dendritic nanotriangle plates (L-type gold nanobranch-type triangle plates or D-type gold nanobranch-type triangle plates), and further obtains anisotropic chiral dendritic nanoparticles (L-type gold nanobranch-type particles or D-type gold nanobranch-type particles). In contrast, achiral gold concave nanotriangle plates (achiral gold nanoconcave triangle plates) were synthesized in the absence of cysteine, which promoted the preferential conformal growth of gold on the side edge facets, resulting in a lack of a specific growth direction, and further obtained achiral gold concave nanoparticles (achiral gold nanoconcave particles).
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The invention is innovative in the field of nanomaterial preparation technology, especially in the application of electrocatalytic oxygen evolution reaction (OXR), showing unique advantages and potential. The following is a detailed description of the key points of the invention:
[0037] (1) Branch-like structure: Gold nanoparticles with branch-like morphology are prepared by carefully controlling the synthesis conditions. This structure not only increases the specific surface area of the material and provides more catalytic active sites, but also its multiple tips can significantly enhance the local electric field effect (tip effect), which helps to accelerate the transmission of electrons on the catalyst surface, thereby improving the catalytic efficiency of the oxygen evolution reaction.
[0038] (2) Nano-size control: Precise control of the size and shape of gold nanoparticles is the key to achieving efficient catalysis. The nanoscale size gives gold particles a higher surface energy, enhancing their interaction with reactants. At the same time, specific shape design (such as branch shape) further optimizes catalytic performance.
[0039] (3) Strong chiral signal: The synthesized gold nanoparticles exhibit strong chiral properties, which are achieved through a specific synthesis method. Chiral materials exhibit unique asymmetry in optical and electrical properties and can affect the spin state of electrons.
[0040] (4) Chirality-induced spin selectivity: The chirality-induced spin selectivity of chiral gold nanoparticles is utilized to act as a spin filter in the catalytic process of oxygen evolution reaction. This effect can selectively transmit electrons with a specific spin state, thereby inhibiting the formation of byproduct hydrogen peroxide, promoting the formation of the target product oxygen, and improving the selectivity and efficiency of the oxygen evolution reaction.
[0041] The present invention combines the structural design of nanomaterials with chiral properties and proposes a novel catalytic strategy for oxygen evolution reaction. By enhancing electron transport and spin selectivity, efficient catalysis of oxygen evolution reaction is achieved, providing a new idea for the design of nanocatalysts.
[0042] The preparation method of the present invention is simple, the manufacturing cost is low, and the catalytic performance of the oxygen evolution reaction is excellent. The chiral catalyst utilizes the spin selectivity effect induced by chirality to inhibit the generation of byproduct hydrogen peroxide in the oxygen evolution reaction, thereby promoting the occurrence of the oxygen evolution reaction. The previously reported chiral catalysts did not show performance differences between the L-type and D-type chirality when catalyzing the oxygen evolution reaction, while the oxygen evolution reaction performance of the L-type gold nano-branched particles in the sample of the present invention is far better than that of the D-type gold nano-branched particles, and is comparable to the performance of the commercial oxygen evolution reaction catalyst ruthenium dioxide. At a current density of 10 milliamperes per square centimeter, the overpotentials of the L-type gold nano-branched particles and the D-type gold nano-branched particles are 355.1 and 449.7 millivolts, respectively, and the Tafel slopes are 61.72 and 149.4 millivolts per decade. The stability test shows that the catalyst of the present invention can maintain stable performance for 24 hours at a current density of 10 milliamperes per square centimeter, and has good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The figure is a comparison of circular dichroism signal intensities prepared at different L-cysteine concentrations in Example 1 of the present invention.
[0044] Figure 2 This is a transmission electron microscope (TEM) image of the L-type gold nanobranched particles prepared in Example 2 of the present invention.
[0045] Figure 3 This is a transmission electron microscope (TEM) image of the D-type gold nanobranched particles prepared in Example 2 of the present invention.
[0046] Figure 4 This is a transmission electron microscope (TEM) image of the achiral gold nanoconcave particles prepared in Example 2 of the present invention.
[0047] Figure 5 Circular dichroism signal diagram of three nanoparticles prepared in Example 2 of the present invention.
[0048] Figure 61 is the X-ray diffraction pattern of three nanoparticles prepared in Example 2 of the present invention.
[0049] Figure 7 A standard three-electrode electrolytic cell for electrochemical water splitting measurements.
[0050] Figure 8 This is the test result of linear sweep voltammetry in Example 3 of the present invention.
[0051] Fig. 9 This is the electrochemical impedance spectroscopy test result in Example 3 of the present invention.
[0052] Fig.10 These are the Tafel slope and overpotential at a current density of 10 mA per square centimeter measured in Example 3 of the present invention.
[0053] Fig.11 To demonstrate the stability of the L-type sample in Example 3 of the present invention, the performance was hardly changed significantly after 1000 scans using cyclic voltammetry.
[0054] Fig.12 To demonstrate the stability of the L-type sample in Example 3 of the present invention, the performance showed almost no significant change when the sample was run at a current density of 10 mA / cm2 for 24 h using chronopotentiometry.
[0055] Fig.13 Schematic diagram of nanoparticles in solution D in Example 1 of the present invention.
[0056] Fig.14 1 is a scanning electron microscope (SEM) image of the L-type gold nano-branched particles prepared in Example 2 of the present invention, wherein (a) and (b) are SEM images of different scales.
[0057] Fig.15 1 is a scanning electron microscope (SEM) image of the D-type gold nanobranched particles prepared in Example 2 of the present invention, wherein (a) and (b) are SEM images of different scales.
[0058] Fig.16 1 is a scanning electron microscope (SEM) image of the achiral gold nanoconcave particles prepared in Example 2 of the present invention, wherein (a) and (b) are SEM images of different scales. DETAILED DESCRIPTION
[0059] The present invention is described in detail below in conjunction with specific embodiments, but is by no means intended to limit the present invention. Features such as preparation methods, materials, structures or composition ratios not explicitly described in this technical solution are considered to be common technical features disclosed in the prior art.
[0060] The following examples will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several modifications and improvements may be made without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.
[0061] The practice of the present invention may employ conventional techniques of chemistry within the skill of the art. In the following examples, efforts have been made to ensure accuracy with respect to the numbers used (including amounts, temperatures, reaction times, etc.), but some experimental errors and deviations should be taken into account.
[0062] The present invention synthesizes chiral multi-branched gold nanoparticles L-type gold nano-branched particles, D-type gold nano-branched particles and corresponding non-chiral catalyst non-chiral gold nano-concave particles for catalyzing oxygen evolution reaction. During the synthesis process, the chirality of the sample can be regulated by regulating the concentration of the chiral ligand, which can be reflected by the circular dichroism signal intensity. The preparation method of the present invention is simple, the manufacturing cost is low, and the catalytic performance of the oxygen evolution reaction is excellent. The chiral catalyst utilizes the chirality-induced spin selectivity effect to inhibit the generation of byproduct hydrogen peroxide in the oxygen evolution reaction, thereby promoting the occurrence of the oxygen evolution reaction. The previously reported chiral catalysts did not show performance differences between the L-type and D-type chirality when catalyzing the oxygen evolution reaction, while the oxygen evolution reaction performance of the L-type gold nano-branched particles in the sample of the present invention is much better than that of the D-type gold nano-branched particles, and is comparable to the performance of the commercial oxygen evolution reaction catalyst ruthenium dioxide. At a current density of 10 mA / cm2, the overpotentials of the L-type gold nanoparticles and the D-type gold nanoparticles were 355.1 and 449.7 mV, respectively, and the Tafel slopes were 61.72 and 149.4 mV / 10. The stability test showed that the catalyst of the present invention could maintain stable performance for 24 hours at a current density of 10 mA / cm2, and had good stability.
[0063] In this embodiment, all reagents used are commercially available reagents.
[0064] Example 1
[0065] This embodiment provides a method for synthesizing chiral gold nanoparticles used as catalysts for oxygen evolution reaction in alkaline water electrolysis, specifically L-type chiral gold nanoparticles, the synthesis method comprising the following steps:
[0066] (1) 0.032 g of tetrachloroauric acid trihydrate and 0.0294 g of trisodium citrate hydrate were added to 20 mL of water, and after mixing, 2 mL of the solution was added to water (36.0 mL), and then an ice-cold sodium borohydride solution (0.1 M, 1.0 mL) was added under magnetic stirring, wherein the temperature of the sodium borohydride solution was 0.5° C. After stirring for 2 minutes, the solution was placed in a water bath at 30° C. for 4 hours, and then placed in a refrigerator at 0 to 2° C. to store the gold seed solution;
[0067] (2) 1 mL of the gold seed solution was added to a mixed solution A containing a cetyltrimethylammonium bromide solution (1 M, 9 mL), a tetrachloroauric acid aqueous solution (0.01 M, 0.25 mL), a sodium hydroxide aqueous solution (0.1 M, 0.05 mL), a potassium iodide aqueous solution (0.01 M, 0.05 mL) and an ascorbic acid solution (0.1 M, 0.05 mL). After mixing evenly under magnetic stirring, 1 mL of the solution was taken and added to a mixed solution containing a cetyltrimethylammonium bromide solution (1 M, 9 mL), a tetrachloroauric acid aqueous solution (0.01 M, 0.25 mL), a sodium hydroxide solution (0.1 M, 0.05 mL). 0.05mL), potassium iodide solution (0.01M, 0.05mL) and ascorbic acid solution (0.1M, 0.05mL) in a mixed solution B, after magnetic stirring and mixing, the whole solution is introduced into a mixed solution C composed of hexadecyltrimethylammonium bromide solution (1M, 90mL), tetrachloroauric acid aqueous solution (0.01M, 2.5mL), sodium hydroxide aqueous solution (0.1M, 0.5mL), potassium iodide aqueous solution (0.01M, 0.5mL) and ascorbic acid solution (0.1M, 0.5mL), the solution is magnetically stirred for 5 minutes, and then water bathed at 30°C for 24 hours. After 24 hours, the product is separated by centrifugation at a speed of 4000-5000rpm for 5 minutes, the supernatant is removed, and the substrate is stored in 1mM100mL hexadecyltrimethylammonium bromide solution to obtain solution D;
[0068] (3) Take 34.77 mL of deionized water, add hexadecyltrimethylammonium bromide solution (8 mL, 10 mmol), tetrachloroauric acid aqueous solution (2 mL, 10 mM) and ascorbic acid solution (5 mL, 40 mM) in sequence, then stir at a speed of 50-100 rpm for 1-2 minutes, inject 3 μL of 1 mM cysteine (cysteine is selected from L-cysteine or D-cysteine, L-cysteine in this embodiment) solution into the solution to form an L-type gold nanobranched triangle or a D-type gold nanobranched triangle, and stir at a speed of 50-100 rpm for 1-2 minutes (for achiral gold nanoconcave triangles, cysteine is not added in this step). Then, 300 to 600 μL of solution D obtained in step (2) was added to the mixed solution and stirred for 30 seconds. The mixture was then placed in a water bath at 30° C. for 1 hour. The obtained chiral gold nanoparticle dispersion was centrifuged at 2500 rpm for 5 minutes to remove unreacted reagents. After removing the supernatant, the mixture was redispersed in 10 mL of 1 mM hexadecyltrimethylammonium bromide solution to obtain chiral gold nanoparticles, which were then stored at room temperature.
[0069] Among them, the preparation method of L-cysteine solution (L-cysteine solution aqueous solution) is as follows: 0.0404g, 0.0505g, and 0.0606g of L-cysteine are added to 20mL of deionized water respectively, and after mixing evenly, 1mL of the just prepared L-cysteine aqueous solution is taken, 11.5mL of deionized water is added, and mixed evenly to obtain 2 / 3mM, 5 / 6mM, and 1mM L-cysteine aqueous solutions respectively.
[0070] When preparing the chiral gold nanoparticles in step (3), three groups of solutions were prepared. 34.77 mL of deionized water was taken from each group. Hexadecyltrimethylammonium bromide solution (8 mL, 10 mmol), tetrachloroauric acid aqueous solution (2 mL, 10 mM) and ascorbic acid solution (5 mL, 40 mM) were added in sequence, and then stirred at a speed of 50-100 rpm for 1-2 minutes. 3 μL of 2 / 3 mM, 5 / 6 mM, and 1 mM L-cysteine aqueous solution were injected into one of the groups of solutions respectively. Stir at a speed of 50-100 rpm for 2 minutes. Then 300-600 μL of the solution obtained in step (2) was added to the mixed solution, stirred for 30 seconds, and then allowed to stand in a water bath at 30°C for 1 hour. The obtained chiral gold nanoparticle dispersion was centrifuged at 2500 rpm for 5 minutes to remove the unreacted reagent. After removing the supernatant, it was redispersed in 10 mL of 1 mM hexadecyltrimethylammonium bromide solution and stored at room temperature to obtain chiral gold nanoparticles. The obtained sample circular dichroism signal intensities were 70 mdeg, 100 mdeg, and 200 mdeg, respectively. Figure 1 shown.
[0071] Example 2
[0072] This embodiment provides a method for synthesizing chiral gold nanoparticles / achiral gold nanoparticles for catalysts for oxygen evolution reaction in alkaline water electrolysis, which is basically the same as the synthesis method in Example 1, except that: when preparing the chiral gold nanoparticles in (3), three groups of solutions are divided, 34.77 mL of deionized water is taken from each group, and hexadecyltrimethylammonium bromide solution (8 mL, 10 mmol), tetrachloroauric acid aqueous solution (2 mL, 10 mM) and ascorbic acid solution (5 mL, 40 mM) are added in sequence, and then stirred at a speed of 50-100 rpm for 1-2 minutes. 3 μL of 1 mM L-cysteine solution and D-cysteine solution are respectively injected into one group of solutions, and no cysteine solution is added to the other group. Stir at a speed of 50-100 rpm for 2 minutes. Then, 300-600 μL of solution D obtained in step (2) is added to the mixed solution, stirred for 30 s, and then allowed to stand in a water bath at 30°C for 1 hour. The obtained chiral gold nanoparticle dispersion (the non-chiral gold nanoparticle dispersion without adding cysteine solution) was centrifuged at 2500rpm for 5 minutes to remove the unreacted reagent, and after removing the supernatant, it was redispersed in 1mM 10mL hexadecyltrimethylammonium bromide solution and stored at room temperature to obtain chiral gold nanoparticles or non-chiral nanoparticles (adding 3μL 1mM L-type cysteine solution to obtain L-type chiral gold nanoparticles, adding 3μL 1mM D-type cysteine solution to obtain D-type chiral gold nanoparticles, and not adding cysteine solution to obtain non-chiral gold nanoparticles). The transmission electron microscopy images of the three groups of samples (specifically, the transmission electron microscopy images are the chiral gold nanoparticles / non-chiral gold nanoparticles after washing the hexadecyltrimethylammonium bromide) are as follows: Figure 2 to Figure 4 , L-type chiral gold nanoparticles are L-type gold nanoparticles with branched shape, D-type chiral gold nanoparticles are D-type gold nanoparticles with branched shape, and achiral gold nanoparticles are achiral gold nanoparticles with concave shape. The circular dichroism signals are as follows: Figure 5 As shown, the obtained chiral nanoparticles L-type gold nanoparticles and D-type gold nanoparticles can detect chiral optical signals. When the absorption is about 0.5-1.5, the circular dichroism signal is 100-150mdeg (relative to the 1mM L-cysteine aqueous solution in Example 1, the optical signal is weaker because the sample concentration during detection is lower than that in Example 1). However, the non-chiral gold nanoparticles with concave triangle shape have no obvious chiral optical signals. When the absorption is about 0.5-1.5, the circular dichroism spectrum is 0-20mdeg.
[0073] The preparation method of D-cysteine solution (D-cysteine aqueous solution) is basically the same as the preparation method of L-cysteine aqueous solution in Example 1: 0.0606 g of D-cysteine is added to 20 mL of deionized water and mixed evenly, then 1 mL of the D-cysteine aqueous solution just prepared is taken, 11.5 mL of deionized water is added, and mixed evenly to obtain a 1 mM D-cysteine aqueous solution.
[0074] Example 3
[0075] The three chiral gold nanoparticles prepared in Example 2 were washed and mixed with hexadecyltrimethylammonium bromide and then drop-casted onto nickel foam to prepare a working electrode. Perfluorosulfonic acid-polytetrafluoroethylene copolymer was used as a binder, and an average of 7 to 8 mg of the sample was dispersed in water and dropped to 1 cm 2 Nickel foam (1×3cm 2 ). The oxygen evolution reaction performance was tested by linear sweep voltammetry and electrochemical impedance spectroscopy. Figure 7 A standard three-electrode electrolytic cell for electrochemical water splitting measurements is shown. The reference electrode and counter electrode are mercury / mercuric oxide (1 M potassium hydroxide) and a carbon rod, respectively. Electrochemical studies were performed using 1 M potassium hydroxide (pH = 14) aqueous electrolyte. Linear sweep voltammetry, electrochemical impedance spectroscopy, overpotential, and Tafel slope are shown in Figure 1. Figure 8 , 9 , 10. In order to test the stability of L-type gold nanoparticles, cyclic voltammetry was performed 1000 times in the system as described above, and the performance was almost unchanged, as shown in FIG. Fig.11 As shown; and the oxygen evolution reaction test was carried out for 24 hours at a current density of 10 mA per square centimeter using the chronopotentiometry, and no significant change in potential was observed, as shown Fig.12 shown.
[0076] Comparison example
[0077] In this comparative example, a commercial catalyst ruthenium dioxide is drop-cast onto nickel foam to prepare a working electrode, and the process of oxygen evolution reaction performance test is the same as that of Example 3.
[0078] In summary, the gold seed solution obtained in step (1) is a solution containing gold seeds, the average particle size of the gold seeds in the gold seed solution is 30 nanometers to 60 nanometers, the nanoparticles in the solution D obtained in step (2) include triangular particles, and the average particle size of the nanoparticles in the solution D is 60 nanometers to 120 nanometers (e.g. Fig.13 As shown in Figures 2 to 4 , 6, 14-16, by scanning electron microscopy ( Figures 14 to 16 )、Transmission electron microscopy( Figures 2 to 4 ) and X-ray diffraction ( Figure 6) characterized the morphology and crystal structure of L / D-type gold nanoparticles and achiral gold nanoparticles. The gold atoms on the small facets on the side edges of the particles follow the island growth mode of chiral gold nanobranched particles, thereby inducing a unique site-selective growth pathway and geometry-dependent chirality. In contrast, achiral gold nanoparticles exhibit a uniform growth pattern of gold atoms along the {111} plane crystal plane of gold without any chiral distortion. The emergence of branches and twigs with clear edges and tips extending from the corners or sides of the triangular nanoplates in a specific direction. This phenomenon not only enhances the chirality of the chiral gold nanobranched particles, but also acts as a spike to attract charges due to the enhanced electric field at the tip. The L-type gold nanobranched particles and D-type gold nanobranched particles obtained in step (3) are snowflake-shaped, with the branches twisted in the clockwise and counterclockwise directions, respectively, and the average particle size is 400 to 600 nanometers. The achiral gold nanoconcave particles are polygonal flat, with no fixed twisting direction, and the average particle size is 300 to 500 nanometers. In addition, high-resolution transmission electron microscopy images provided valuable insights into the chirality of the atomic lattice structure. Given that the charge mainly accumulates at the dendrite tips during the electrochemical measurements, the lattice structure of these tips was specifically investigated. The L-type gold nanobranch particles exhibited a polycrystalline structure, and lattice spacings of 0.198nm, 0.219nm, and 0.237nm were observed at the dendrite tips. Similarly, the D-type gold nanobranch particles showed lattice spacings of 0.198nm, 0.217nm, and 0.239nm, which were very similar to those of the L-type gold nanobranch particles. However, the lattice spacings of the achiral gold nanoconcave particles (0.201nm, 0.219nm, and 0.226nm) slightly deviated from those of the chiral gold nanobranch particles, with a smaller maximum lattice spacing and a larger minimum lattice spacing. This indicates that the chiral species has a lattice distortion, resulting in a decrease in the lattice spacing perpendicular to the distortion and an increase in the spacing parallel to the distortion.
[0079] X-ray diffraction patterns (XRD) were used to investigate whether there were lattice changes in chiral crystals. The main peaks of the XRD patterns of the three species were (1 1 1), which was consistent with the results of high-resolution transmission electron microscopy. There was no significant difference in the XRD patterns of the L-type gold nanobranched particles and the D-type gold nanobranched particles. In addition, the peaks of the chiral crystals and the achiral crystals were almost identical, indicating that chirality did not change the type of crystal planes.
[0080] X-ray photoelectron spectroscopy was used to detect binding energy and valence state. The gold 4f 7 / 2 and 4f5 / 2 peaks of L-type gold nanobranch particles are located at 83.62 and 87.3 eV, and the two peaks of D-type gold nanobranch particles are located at 83.66 and 87.33 eV, so there is almost no difference in the binding energy between L-type gold nanobranch particles and D-type gold nanobranch particles. However, compared with achiral gold nanoparticles (gold 4f7 / 2 is 83.45 eV and gold 4f 5 / 2 is 87.12 eV), the binding energy of chiral gold nanoparticles is slightly shifted to a higher binding energy of about 0.15 eV. This suggests that the chiral distortion of the lattice may affect the charge distribution and lead to higher binding energy, which means that for chiral species, the core may have a stronger electron affinity and more stably bind to the surrounding electrons, which helps to regulate adsorption and desorption during catalytic reactions.
[0081] like Fig.10 As shown, the excellent oxygen evolution reaction activity of L-type gold nanobranch particles can be verified by their low overpotential and Tafel slope. When the current density is 10 mA per square centimeter, the overpotential of L-type gold nanobranch particles is 355.7 mV, which is even lower than the overpotential of commercial catalysts ruthenium dioxide (387.7 mV), D-type gold nanobranch particles (449.1 mV) and non-chiral gold nanoconcave particles (455.3 mV). The Tafel slope, that is, the rate of change of potential with the logarithm of current density, reveals the electrochemical exchange current and reaction kinetics of a specific catalyst. The Tafel slope of L-type gold nanobranch particles at 10 mA per square centimeter is 61.72 mV per decade, which is significantly lower than the 136.76 mV per decade of commercial catalysts. For D-type gold nanobranch particles and non-chiral gold nanoconcave particles, their Tafel slopes are 149.4 mV per decade and 228.0 mV per decade, respectively.
[0082] The above is a description of the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above-mentioned description of the embodiments for the convenience of ordinary technicians in the technical field to understand and use the invention. It is obvious that those familiar with the technology in the field can easily make various modifications to these embodiments and apply the general principles described here to other embodiments without creative work. Therefore, the present invention is not limited to the above-mentioned embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.
Claims
1. A method for synthesizing chiral gold nanoparticles for use as catalysts for oxygen evolution reaction in alkaline water electrolysis, characterized in that: The synthesis method comprises the following steps: (1) adding tetrachloroauric acid trihydrate and trisodium citrate hydrate to water, mixing the mixture, adding the mixture to water, then adding ice-cold sodium borohydride solution under stirring, heating the solution in a water bath after stirring, and then storing the gold seed solution at low temperature; (2) adding the gold seed solution obtained in step (1) to a mixed solution A containing cetyltrimethylammonium bromide, tetrachloroauric acid, sodium hydroxide, potassium iodide and ascorbic acid, stirring and mixing them uniformly, taking the mixed solution, adding it to a mixed solution B containing cetyltrimethylammonium bromide, tetrachloroauric acid, sodium hydroxide, potassium iodide and ascorbic acid, stirring and mixing them uniformly, and then introducing the entire solution into a mixed solution C composed of cetyltrimethylammonium bromide, tetrachloroauric acid, sodium hydroxide, potassium iodide and ascorbic acid, stirring the solution, then heating it in a water bath, centrifuging the product, removing the supernatant, and storing the substrate in the cetyltrimethylammonium bromide solution to obtain a solution D; (3) Take water, add hexadecyltrimethylammonium bromide, tetrachloroauric acid and ascorbic acid in sequence, then stir, inject the cysteine solution into the solution to form a gold nanotriangle, stir for 1 to 2 minutes, then take the solution D obtained in step (2) and add it to the mixed solution, stir, and then stand in a water bath to obtain a chiral gold nanoparticle dispersion, centrifuge the obtained chiral gold nanoparticle dispersion to remove unreacted reagents, remove the supernatant, and redisperse in the hexadecyltrimethylammonium bromide solution to obtain chiral gold nanoparticles.
2. The method for synthesizing chiral gold nanoparticles for an alkaline water electrolysis oxygen evolution reaction catalyst according to claim 1, characterized in that: The gold seed solution obtained in step (1) is a solution containing gold seeds, and the average particle size of the gold seeds in the gold seed solution is 30 nanometers to 60 nanometers.
3. The method for synthesizing chiral gold nanoparticles for an alkaline water electrolysis oxygen evolution reaction catalyst according to claim 1, characterized in that: The nanoparticles in solution D obtained in step (2) are triangular particles, and the average particle size of the nanoparticles in solution D is 60 nanometers to 120 nanometers.
4. The method for synthesizing chiral gold nanoparticles for an alkaline water electrolysis oxygen evolution reaction catalyst according to claim 1, characterized in that: In step (3), when the cysteine in the cysteine solution is L-cysteine, the chiral gold nanoparticles formed are L-type gold nanobranch particles, the L-type gold nanobranch triangles are snowflake-shaped, the branches twist in a clockwise direction, and the average particle size is 400 to 600 nanometers.
5. The method for synthesizing chiral gold nanoparticles for an alkaline water electrolysis oxygen evolution reaction catalyst according to claim 1, characterized in that: In step (3), when the cysteine in the cysteine solution is D-type cysteine, the chiral gold nanoparticles formed are D-type gold nanobranch particles, and the D-type gold nanobranch triangle is snowflake-shaped, with the branches twisted in the counterclockwise direction and an average particle size of 400 to 600 nanometers.
6. The method for synthesizing chiral gold nanoparticles for alkaline water electrolysis oxygen evolution reaction catalyst according to claim 1, characterized in that: The chiral gold nanoparticles obtained in step (3) are chiral gold nanoparticles capable of detecting chiral optical signals, and when the absorption is about 0.5 to 1.5, the circular dichroism signal is 100 to 200 mdeg; The main crystal plane of the chiral gold nanoparticles obtained in step (3) exposed in the X-ray diffraction characterization is the gold (11 1) crystal plane.
7. The method for synthesizing chiral gold nanoparticles for an alkaline water electrolysis oxygen evolution reaction catalyst according to claim 1, characterized in that: The synthesis method specifically comprises the following steps: (1) 0.0256-0.0384 g of tetrachloroauric acid trihydrate and 0.02352-0.03528 g of trisodium citrate hydrate were added to 20 mL of water, and after mixing, 2 mL of the solution was added to 36.0 mL of water, and then 1.0 mL of 0.1 M ice-cold sodium borohydride solution was added under magnetic stirring, wherein the temperature of the sodium borohydride solution was 0.5° C. After stirring for 2 minutes, the solution was placed in a water bath at 30° C. for 4 hours, and then placed in a refrigerator at 0-2° C. to store the gold seed solution; (2) 0.5 mL to 2 mL of the gold seed solution was added to a mixed solution A containing 9 mL of 0.05-1 M hexadecyltrimethylammonium bromide, 0.25 mL of 0.01 M tetrachloroauric acid, 0.05 mL of 0.1 M sodium hydroxide, 0.05 mL of 0.01 M potassium iodide and 0.05 mL of 0.1-0.2 M ascorbic acid. After mixing evenly with magnetic stirring, 1 mL of the solution was taken and added to 9 mL of 0.05-1 M hexadecyltrimethylammonium bromide, 0.25 mL of 0.01 M tetrachloroauric acid, 0.05 mL of 0.1M sodium hydroxide, 0.05mL of 0.01M potassium iodide and 0.05mL of 0.1-0.2M ascorbic acid were mixed in a mixed solution B, and after being uniformly mixed by magnetic stirring, the whole solution was introduced into a mixed solution C composed of 90mL of 0.05-1M hexadecyltrimethylammonium bromide, 2.5mL of 0.01M tetrachloroauric acid, 0.5mL of 0.1M sodium hydroxide, 0.5mL of 0.01M potassium iodide and 0.5mL of 0.1-0.2M ascorbic acid, and the solution was magnetically stirred for 5 minutes, and then water bathed at 30°C for 24 hours. After 24 hours, the product was separated by centrifugation at a speed of 4000-5000rpm for 5 minutes, the supernatant was removed, and the substrate was stored in 1mM 100mL hexadecyltrimethylammonium bromide solution to obtain solution D; (3) Take 34.77 mL of deionized water, add 8 mL of 10 mmol hexadecyltrimethylammonium bromide, 2 mL of 10 mM tetrachloroauric acid and 5 mL of 40 mM ascorbic acid in sequence, then stir at a speed of 50-100 rpm for 1-2 minutes, inject 3 μL of 0.5-1 mM cysteine solution into the solution to form a gold nanobranch-shaped triangle, stir at a speed of 50-100 rpm for 1-2 minutes, then take 300-600 μL of solution D obtained in step (2) and add it to the mixed solution, and stir for 30 seconds, then stand in a water bath at 30°C for 1 hour, centrifuge the obtained chiral gold nanoparticle dispersion at 2500 rpm for 5 minutes to remove unreacted reagents, remove the supernatant, and redisperse it in 1 mM 10 mL hexadecyltrimethylammonium bromide solution to obtain chiral gold nanoparticles, which are stored at room temperature.
8. A chiral gold nanoparticle used as a catalyst for oxygen evolution reaction in alkaline water electrolysis, characterized in that: The chiral gold nanoparticles are prepared by the synthesis method for the catalyst of the alkaline water electrolysis oxygen evolution reaction as described in any one of claims 1 to 7.
9. An application of chiral gold nanoparticles prepared by the synthesis method according to any one of claims 1 to 7 as a catalyst for oxygen evolution reaction in alkaline water electrolysis, characterized in that: The chiral gold nanoparticles are used as catalysts for oxygen evolution reaction in an alkaline electrolyte.
10. The use according to claim 9, characterized in that: At a current density of 10 mA / cm2, the overpotential of the chiral gold nanoparticles is 355.7 mV to 449.1 mV; The Tafel slope of the chiral gold nanoparticles at 10 mA / cm2 is 61.72 mV / decade to 149.4 mV / decade.
Citation Information
Patent Citations
Gold nanoparticle triangular plate preparing method and method for preparing gold nanoparticle discs and gold nanoparticle hexagonal pieces on basis of gold nanoparticle triangular plate preparing method
CN104625086A
Discrete precious metal nanoparticles and preparing method thereof
CN106238728A
Preparation method and application ofchiral nanochannels of photoswitch
CN110044979A
Metal nanostructure and method for producing same
CN110573280A
Three-dimensional chiral nanostructures
CN110582361A